OPTIMALISASI GOOD GOVERNMENT MELALUI STANDARISASI PELAYANAN PUBLIK - Novita Maulida Ikmal; Indriastuti Indriastuti (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Currently, problems related to public services are still far from being expected and must continue to be improved. In realizing good governance today, it is needed not only good public services in local and central governments, but also in sub-district governments. There are three important reasons behind the novelty of public services as an effort to encourage good governance practices in Indonesia. First, improving the performance of public services that are considered important by stakeholders, namely the government, the community and the business world. Second, public service is the domain of the three elements of government that interact very intensively. Third, the values ​​that characterize the practice of administering government are translated more easily and clearly through public services.The implementation of the Community Empowerment Program (PPM) includes the format, socialization activities in collaboration with the Immigration Office Class I TPI Tanjung Perak with the theme Strengthening Public Services in Realizing Good Governance in Government Offices. Strengthening public services under supervision in three stages. The first stage is sharing discussion, FGD activities, and preparing public service standardization. The target of this activity is all village officials. From these socialization activities resulted in the standardization of public services that have been made jointly based on Law No. 25 of 2009 and Ministerial Regulation No. 36 of 2012. Simple Public Service Principles; certainty of time; accuracy; legal certainty; responsibility; facilities and infrastructure; easy access; discipline, manners and registration; as well as convenience. In addition, it is also determined by service techniques in the urban village sector. Keywords: Optimization, Good Government, Public Service. Standardization